(untitled) (Eurasian Journal of Philology Science and Education, 2015)
Anatolia Turkish folk play and spectacles assume importance with its the entertaining and training towards which are irreplaceable and valuable examples of the people thinking and courage of humour, imitation, song, dance, word and word play. The Anatolia Turkish folk play and spectacles which have ancient history have spread under the name of "Seyirlik köy oyunları", "Kukla", "Meddahlık", "Karagöz" and "Ortaoyunu" widely. By describing of playing rules of this play and spectacles, it is given brief information about their similarity and different peculiarities, the general features, the origin and what meaning attainted in the article.